(untitled) (Trabalho & Educação, 2018)
In this text, we seek to analyze how a teacher of the first years of elementary education, from a state public school located in Maceió/AL, develops the style and catachresis when carrying out her teaching activity in precarious working conditions. The theoretical-methodological assumptions guiding the research are the Historical-Cultural theory and the Activity Clinic. Style and catachresis are categories developed by the Clinic of Activity and represent part of the singularity of the subject when developing their professional activity, the style being the personal mode of appropriation of the collective gender of the work and catachresis a symbolic and instrumental (re) creation of professionals in searching of improvements to its activity. We used, as procedures of data collection, observations, interviews and Simple Autoconfrontation. We identified that, in a context of extreme limitations and problems, the teacher tended to present a traditional style, bringing her subjectivity as a central aspect of her teaching activity, reproducing previous educational experiences, and, consequently, a catachresis that became ineffective by a Pedagogical point of view, impairing their activity with children and their own professional growth. ___ Neste texto buscamos analisar como uma professora dos anos iniciais do ensino fundamental, de uma escola pública estadual localizada em Maceió/AL, desenvolve o estilo e a catacrese ao realizar sua atividade docente em condições de trabalho precárias. Os pressupostos teórico- metodológicos orientadores da pesquisa são a teoria Histórico-cultural e a Clínica da Atividade. Estilo e catacrese são categorias desenvolvidas pela Clínica da Atividade e representam parte da singularidade do sujeito ao desenvolver sua atividade profissional, sendo o estilo o modo pessoal de apropriação do gênero coletivo do trabalho e catacrese uma (re)criação simbólica e instrumental do profissional em busca de melhorias para sua atividade. Utilizamos, como procedimentos para coleta de dados observações, entrevistas e Autoconfrontação Simples. Identificamos que, em contexto de limitações e problemas extremos, a professora tendeu a apresentar um estilo tradicional, trazendo a sua subjetividade como aspecto central na sua atividade docente, reproduzindo experiências educacionais passadas e, em decorrência, uma catacrese que se torna pouco efetiva do ponto de vista pedagógico, prejudicando a sua atividade com as crianças e seu próprio crescimento profissional.